Four ways in which data-free papers on animal personality fail to be impactful - DiRienzo, Nicholas; Montiglio, Pierre-Olivier (Frontiers in Ecology and Evolution, 2015)
The literature on animal personality is dominated by papers lacking any data. These papers, which we will call ‘data-free’ papers, are cited and recognized twice as much as comparable empirical studies. In this data-free paper, we highlight 4 common data-free contributions that often fail to have an impact on the topic: a) novel conceptual frameworks suggesting novel avenues of research or hypotheses, b) papers prescribing novel terminologies, c) syntheses revisiting older theories, and d) papers introducing novel statistical methods. We argue that conceptual papers presenting a novel hypothesis probably could almost always be replaced by robust empirical studies actually testing the hypotheses of interest. We hope this paper will stimulate discussion on what makes a data-free paper on animal personality impactful, beyond simply being highly cited.